Correlation and heritability Analysis in the genetic improvement of camu-camu - Pinedo Panduro, Mario (2012)
In Peru and Brazil have been made between 2002 and 2011, correlation and heritability in search of tools for genetic improvement of camu-camu. We studied basic collections, comparative and progeny clones exist in the INIA, IIAP and INPA. The length of petiole (LP), has a half heritability (in the broad sense) of h2 g = 0.42 and correlation coefficients of r2 = 0.37 with fruit yield and r2 = 0.54 with fruit weight. Basal branch number (NRB) also shows levels of heritability average (in the strict sense): h2a = 0.45 and h2g = 0.33 in the broad sense. NRB in turn significantly correlated with fruit yield (RF) (r2 = 0.43), fruit weight (FW) (r2 = 0.38) and ascorbic acid (AA) (r2 =- 0.30). The values of pH and soluble solids (degrees Brix) of the pulp showed a high correlation with AA (r2 = 0.85 and r2 = 0.94 respectively). In light of the information correlation and heritability, we emphasize that the parameters "number of basal branches", "petiole length" and "fruit weight" and present a relatively high correlation with "yield fruit" also have a level intermediate heritability, which qualify them as important tools for the selection of superior plants camu-camu.